The design paradox: the contribution of in-house and external design activities on product market performance - Dirk Czarnitzki; Susanne Thorwarth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper explores the contribution of design activities on product market performance of Belgian companies. While there is mounting evidence that design can be seen as a strategic tool to successfully spur sales of new product developments at the firm level, the topic of design innovation has not been linked to the open innovation concept yet. In this paper we empirically test whether design activities conducted in-house differ in their contribution to new product sales from externally acquired design. Using a large crosssection of manufacturing and service firms, we investigate the effects on sales of products new to the market and of imitation or significantly improved products of the firm. At first glance, we find the paradox that externally acquired design is not superior to in-house design activities. This effect is robust to several modifications of the model specification. As earlier literature on new technological developments in high-tech sectors, we argue, however, that external design may not affect the sales of market novelties as the "market news" may spill-over quickly to rivals through common customers and suppliers including external designers.
Keywords: O31; O32; 330; Design; R&D; Collaboration; Open Innovation; Product Market Performance; Produktdesign; Industrielle Forschung; Innovation; Make or Buy; Innovationsdiffusion; Absatz; Belgien